Tracoma: ainda uma importante causa de cegueira - Schellini, Silvana Artioli [UNESP]; Lilian, Roberta; de Sousa, Fernandes (Soc Brasileira Oftalmologia, 2012)
Trachoma is a disease known thousand years ago and still as a potential blindness disease all over the world. The authors call attention to the factors related with the transmission, present historical data and distribution of the disease in Brazil and in the world, comment on the agent, the signs and symptoms of this chronic conjunctivitis. Still, reinforce the need to enable professionals for the diagnosis, detection and treatment. The reflection of these attitudes will be the contribution to the elimination of this important disease as a blindness cause among us.

O Tracoma é uma doença milenarmente conhecida e que persiste como causa de cegueira entre nós. As autoras chamam a atenção para os fatores relacionados com a transmissão, apresentam dados históricos e de distribuição da doença no Brasil e no mundo, comentam sobre o agente, os sinais e os sintomas desta conjuntivite crônica. Ainda reforçam a necessidade de capacitar os profissionais para o diagnóstico, o que possibilitará a detecção e tratamento. O reflexo destas atitudes será a contribuição para a eliminação desta importante causa de cegueira do nosso meio.
Trachoma: still being an important blinding disease
Keywords: Trachoma/history; Chronic conjunctivitis; Blindness; Brazil